Assessing Tourism Destination Development through The TALC Framework: A Study of TEFA Kebun Inovasi Polije - Farhan, Muhamad; Wardani, Peni Arianita; Rachman, Nur Afni; Rahmanita, Meiga; Putri, Astrid Hidayanti Ananda; Wahyudi, Eghy Danuarta Putra; Mujiyati, Debby Dwi (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
The development of TEFA Kebun Inovasi has the potential to serve as a model for agrotechnotropical-based tourism, providing an educational platform for visitors and the community about the application of agricultural technology and its practical benefits in daily life. However, a comprehensive analysis of the current conditions is necessary to ensure that strategic actions are aligned with the appropriate stages of development. This study aims to analyze the development phase of TEFA Kebun Inovasi Polije through the lens of the Tourism Area Life Cycle (TALC) framework, which encompasses seven phases: exploration, involvement, development, consolidation, stagnation, decline, and rejuvenation. The research employs a descriptive qualitative approach, utilizing data collection methods such as observation, interviews, and documentation. The findings indicate that TEFA Kebun Inovasi is currently in the development phase that characterize with initiating facility investments, introducing additional attractions, enhancing promotional efforts, and planning for product diversification. Nevertheless, several characteristics of involvement phase still appear including few tourists’ arrival, basic promotional activities, and a reliance on the limited primary attraction mark the involvement phase. The results of this research are intended to inform the ongoing development of TEFA Kebun Inovasi and contribute to the study of agrotourism destinations on campus.